Gluten-free food science and technology - Gallagher, Eimear (Wiley-Blackwell, 2009)
Provides an overview for the food industry of issues related to the prevalence of coeliac disease and gluten intolerance. This work discusses the properties of gluten in relation to its classification and also addresses important functional characteristics, and the nutritional value of gluten-free products.